PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT MUSASHI - Putra, Paris Sansony; Suryaman, Dede Jajang; Nurhasanah, Nunung (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
Thisl study aimsl to examinel the influencel of leadershipl style andl work motivationl on employeel performance at PT Musashi, bothl partially andl simultaneously. Al quantitative approachl was employed using an associative method to analyze the relationship among thel variables: leadershipl style (X1l), work motivationl (X2), andl employee performancel (Y). Thel sampling technique applied was purposive sampling, involving 200 permanent employees as respondents. Data werel collected throughl observations and the distributionl of questionnairesl utilizing a Likertl scale. Thel results ofl the analysisl indicate thatl both independent variables havel a positivel and significantl influence onl employee lperformance, both individually andl jointly. Thel Adjusted Rl-Square valuel of 0.728 suggests thatl 72.8% of thel variation inl employee performancel can bel explained by leadership style and work motivation, while the remaining 27.2% is attributed to other factors beyond the scope of this study. These findings highlight the importance of implementing an effective leadership style and consistently enhancing work motivation to improve employee performance. The study offers practicall implications forl company managementl to prioritize leadershipl development and motivationall strategies within the workplace environment.